A TEST OF FIT FOR LINDLEY DISTRIBUTION - Alizadeh Noughabi, Hadi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
It is important to develop efficient goodness of fit test for Lindley distribution because it is one of the fundamental models applied for reliability models. This article introduces some test statistics for examining the Lindley goodness of fit based on the empirical distribution function. Critical points and the power of the tests are obtained by Monte Carlo simulation. We show that the proposed tests have a good performance against different alternatives, and therefore, these tests can be confidently used in practice. Finally, the proposed tests are illustrated by a real data example.